NBA1, a new player in the Brca1 A complex, is required for DNA damage resistance and checkpoint control - Wang, Bin (Cold Spring Harbor Laboratory Press, 2009)
The ability to sense and respond to DNA damage is critical to maintenance of genomic stability and the prevention of cancer. In this study, we employed a genetic screen to identify a gene, NBA1 (new component of the BRCA1 A complex), that is required for resistance to ionizing radiation. The NBA1 protein localizes to sites of DNA damage and is required for G2/M checkpoint control. Proteomic analysis revealed that NBA1 is a component of the BRCA1 A complex, which also contains Brca1/Bard1, Abra1, RAP80, BRCC36, and BRE. NBA1 is required to maintain BRE and Abra1 abundance and for the recruitment of BRCA1 to sites of DNA damage. In depth bioinformatics analysis revealed that the BRCA1 A complex bears striking similarities to the 19S proteasome complex. Furthermore, we show that four members of the BRCA1-A complex possess a polyubiquitin chain-binding capability, thus forming a complex that might facilitate the deubiquitinating activity of the deubiquitination enzyme BRCC36 or the E3 ligase activity of the BRCA1/BARD1 ligase. These findings provide a new perspective from which to view the BRCA1 A complex.